2005
DOI: 10.1177/0091270004271094
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Oropharyngeal Deposition of Inhaled Ciclesonide and Fluticasone Propionate in Patients With Asthma

Abstract: Ciclesonide is a novel inhaled corticosteroid that is converted in the lungs to its active metabolite, desisobutyryl-ciclesonide (des-CIC). The aim of this study was to compare the deposition of ciclesonide, as well as its conversion to des-CIC, in the oropharyngeal cavity with fluticasone propionate (FP) following inhalation via hydrofluoroalkane-propelled metered-dose inhalers (HFA-MDIs). Eighteen asthmatics inhaled ciclesonide 800 microg followed by FP 1000 microg or vice versa in an open, randomized, 2-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 15 publications
(13 reference statements)
2
64
0
1
Order By: Relevance
“…Furthermore, the concentration of des-CIC in the oropharynx was 25-fold lower than that of BUD [44]. In a similar study comparing ciclesonide (800 mg ex-valve) and FP (1,000 mg) in patients with asthma, the oropharyngeal deposition of ciclesonide and des-CIC together was approximately half that of FP, and the deposition of des-CIC was only 8% of that of FP [45]. This lower oropharyngeal deposition and minimal activation to des-CIC leads to a reduced occurrence of local side-effects (e.g.…”
Section: Formulation and Particle Sizementioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, the concentration of des-CIC in the oropharynx was 25-fold lower than that of BUD [44]. In a similar study comparing ciclesonide (800 mg ex-valve) and FP (1,000 mg) in patients with asthma, the oropharyngeal deposition of ciclesonide and des-CIC together was approximately half that of FP, and the deposition of des-CIC was only 8% of that of FP [45]. This lower oropharyngeal deposition and minimal activation to des-CIC leads to a reduced occurrence of local side-effects (e.g.…”
Section: Formulation and Particle Sizementioning
confidence: 88%
“…Ciclesonide has a much lower RRA (12) than des-CIC (1,200), and is, therefore, virtually pharmacologically inactive [24]. Studies have indicated that bioactivation of ciclesonide within the oropharynx is very low, resulting in lower amounts of active drug in the oropharyngeal region compared with BUD and FP [44,45].…”
Section: Mometasone Furoate 2200mentioning
confidence: 99%
“…des-CIC, which has high local antiinflammatory activity in the lung, is conjugated to fatty acids to prolong anti-inflammatory activity in the lung, is essentially devoid of oral bioavailability, has high protein binding in the systemic circulation, and is rapidly and completely eliminated from the body (Dietzel et al, 2001). Recent data suggest that the oropharyngeal deposition of ciclesonide is only half that of fluticasone with little activation to des-CIC following inhalation from a hydrofluoro-alkane-propelled metered-dose inhaler in asthmatics, suggesting a decreased likelihood of ciclesonide-associated side effects (Richter et al, 2005).…”
Section: Ciclesonide a Novel Corticosteroid 571mentioning
confidence: 99%
“…In a study of adults with bronchial asthma, the oropharyngeal deposition of ciclesonide was about 50% of that reported with fluticasone propionate, with 90% less des-CIC present in the oropharyngeal cavity compared with fluticasone following inhalation (Richter et al 2005). Following administration of ciclesonide and budesonide to healthy volunteers, the maximal concentrations of ciclesonide and des-CIC recovered from oropharyngeal wash were 30% and 0.67% of budesonide, respectively (Nave et al 2005a).…”
Section: Systemic Absorptionmentioning
confidence: 97%